Application of difierent doses of Kaliumax foliar fertilizer in the cultivation of castilla beans (Vigna unguiculata L.) to improve its yield - Legua Cárdenas, José Antonio (2019)
The present investigation used Kaliumax foliar fertilizer in the cultivation of castilla beans, experimental tests were carried out in an agricultural soil of the city of Barranca, and aimed to determine which dose of Kaliumax achieves greater yield. In the experimental practice the treatments were fixed according to the practical information used by the farmers, these were T1 = 00, T2 = 0,5, T3 = 1,0, T4 = 1,5 l. Kaliumax / 200 l, the application to the crop was made at 37, 51 and 65 days. The statistical model that was used was the Completely Random Block Design with four treatments and four blocks and the data was processed with Duncan Analysis of Variance and Test. Once the results were obtained, it was determined that T3 stood out in flower / plant count with 28,41 flowers; pod count with physiological maturity 18,07 pods; average pods / plant with 44,31 pods; pod weight / plant 112,45 g; commercial yield with 2,79 tn / ha. In the laboratory, T4 stood out with foliar analysis of 3,50 g / 100 g dry matter, as for T3 it stood out in length of sheath with 16,15 cm and weight of 100 grains per sample with 22,10 g. Regarding the economic aspect, the highest cost / benefit was achieved in Q3 with S/ 0,52